Species diversity of Rhizophora in Tambelan Islands, Natuna Sea, Indonesia - AHMAD DWI SETYAWAN; YAYA IHYA ULUMUDDIN (Society for Indonesian Biodiversity, 2012)
Setyawan AD, Ulumuddin YI. 2012. Species diversity of Rhizophora in Tambelan Islands, Natuna Sea, Indonesia. Biodiversitas 13:172177.Â ResearchÂ onÂ diversityÂ andÂ distributionÂ ofÂ mangrovesÂ onÂ theÂ smallÂ remoteÂ islandsÂ areÂ rarelyÂ performedÂ thanÂ onÂ theÂ coastalÂ areaÂ andÂ estuaries. Tambelan Islands is a cluster of small islands isolated in the Natuna Sea, Indonesia. On the island there are four species of Rhizophora, namely R. apiculata, R. stylosa, R. mucronata, and hybrid species R. x lamarckii. Rhizophora stylosa and R. apiculata are the most common species found. R. mucronata only found in certain places (i.e. Durian River), R. x lamarckii rare, usually grows in stands that also covered by the two parental, R. stylosa and R. apiculata. All Rhizophora species were found to have thorn on the leaf tip, and spotted brown on the underneath leaf. R. apiculata has a petal without woolly feathers, inflorescence have short stalks and cork. R. stylosa and R. mucronata are sibling species, both of them have a long-stalks and dichotomy inflorescence, but the style of R.Â mucronata very short (<2.5 mm),Â whereas in R. stylosa longer (> 2.5 mm). R. x lamarckii has characters between R. apiculata and R. stylosa.